Comparison of different contact force models for low and moderate impact velocities: numerical and experimental analysis - Flores, Paulo (2013)
It has been recognized by many theoretical and experimental investigations that the constitu- tive contact force law considered to model and analyze contact-impact phenomena is of paramount im- portance in the prediction of the dynamic behavior of mechanical systems. The main goal of this work is to present a numerical and experimental comparative study on different compliant contact force models. The contact force models utilized in this study are based on the classical Hertzian contact the- ory, which is augmented with damping terms to accommodate the energy loss during the impact proc- ess. The classical impact between a steel ball and a massive surface is used as the demonstrative exam- ple of application. The influence of the initial impact velocity and coefficient of restitution is also studied throughout this work.